2021
DOI: 10.3390/nu13113707
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations between Dietary Daily Nicotinamide Intake and Patient-Reported Outcomes in Colorectal Cancer Survivors, 2 to 10 Years Post-Diagnosis

Abstract: Supplementation with nicotinamide adenine dinucleotide (NAD+) precursors including dietary nicotinamide has been found to boost tissue NAD+ levels and ameliorate oxidative stress-induced damage that contributes to aging and aging-related diseases. The association between dietary NAD+ precursors and patient-reported health-related outcomes in cancer survivors has not been investigated. This study aimed to determine associations of dietary nicotinamide intake with different patient-reported outcomes in colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
1
2
Order By: Relevance
“…It is reported that CRC survivors who received a dietary intervention had significantly lower levels of depression, but no significant changes in the levels of anxiety 28 . A study finds that dietary daily nicotinamide reduced the levels of anxiety and depression in men 56 . However, the results of this study showed that there were no significant differences in the levels of depression and anxiety between the lifestyle intervention group and the control group.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It is reported that CRC survivors who received a dietary intervention had significantly lower levels of depression, but no significant changes in the levels of anxiety 28 . A study finds that dietary daily nicotinamide reduced the levels of anxiety and depression in men 56 . However, the results of this study showed that there were no significant differences in the levels of depression and anxiety between the lifestyle intervention group and the control group.…”
Section: Discussioncontrasting
confidence: 54%
“…28 A study finds that dietary daily nicotinamide reduced the levels of anxiety and depression in men. 56 However, the results of this study showed that there were no significant differences in the levels of depression and anxiety between the lifestyle intervention group and the control group. Small sample size and ceiling effects may have limited the ability of the included studies to detect the improvement of depression and anxiety.…”
Section: Discussioncontrasting
confidence: 52%
“…The second human clinical study investigated the effects of NMN intake (250 mg/day) in obese postmenopausal women with prediabetes (NMN = 13, placebo = 12) for 10 weeks in a randomized, placebo-controlled, double-blind trial, reporting that significant improvement was found in protein kinase AKT, mTOR protein, and insulin sensitivity, whereas no significant changes were found in grip strength, fatigability, and recovery from the fatiguing exercise of the leg [23]. On the contrary, in a cross-sectional study, daily intake of dietary nicotinamide, which has a different salvage pathway from NMN, was reported to be significantly associated with not only higher grip strength but also lower subjective fatigue in colorectal cancer survivors [33]. In this study, despite the non-significant change in grip strength, NMN intake in the afternoon was effective in improving drowsiness among several factors of subjective fatigue.…”
Section: Discussionmentioning
confidence: 93%